Assessment of customer satisfaction at the University of Limpopo using servqual model - Rikhotso, Sandile Sindile Buwazi (My University, 2024)
Service quality plays an integral role in the Higher Education Institution’s reputation, competitiveness and most importantly in students’ satisfaction. Service quality in the Higher Education Institutions (HEIs) distinguishes one institution from another, and its assessment can lead to a competitive advantage and the development of marketing and business initiatives. If students are not satisfied with the quality of services being offered by the university, they are likely not to recommend others through word of mouth to enrol at that institution, it can tarnish the brand image of the institution, and it may not attract future students which will ultimately has a negative impact on the financial state of the institution. This study was then conducted to assess customer satisfaction of the administrative services that are provided to the University of Limpopo students using the SERVQUAL model. The study was designed in such a way to begin the process of determining the students’ expectations of the services and how they perceive the quality of administration services after receiving them as well as evaluating the level of satisfaction of these services provided by the employees of the institution. A better understanding of whether the students’ expectations are met or not, would then assist the institution in improving the quality of their services provided to students if they are found to be lacking, a quantitative, descriptive approach was conducted to determine whether students at the university of Limpopo are satisfied or dissatisfied with the administration services provided by the university’s central administration offices. Self-administered online and physical questionnaires were utilised to collect data for the study. The questions were based on the SERVQUAL model where a first set of questions were based on the expectations on service quality, the second set were based on the perceptions of service received across all the dimensions of the model namely tangibility, reliability, responsiveness, assurance and empathy. A total number of 288 students participated in the study. The overall findings revealed that students are dissatisfied with the quality of administration services provided by the University of Limpopo’s central administration offices across all dimensions of the SERVQUAL model. This was determined by the low perceptions scores of service quality as compared to the expectations scores. Therefore, the study recommended an improvement of service quality in order to enhance the students’ satisfaction
Thesis (MBA.) -- University of Limpopo, 2024
Keywords: Customer satisfaction; Customer expectations; Customer perceptions; Service quality; Consumer satisfaction; SERVQUAL (Service quality framework)